Reactions with hydrazonoyl halides 65: Synthesis of some new 1,3,4-thiadiazoles and triazolino[4,3-a]pyrimidines containing pyrazole moiety - Abdelhamid, Abdou Osman; Fahmi, Abdelgawad Ali; Halim, Karema Noury Mahmoud (European Journal of Chemistry, 2011)
2,3-Dihydro-1,3,4-thiadiazoles, and triazolino[4,3-a]pyrimidines containing pyrazole moieties were prepared from the reaction of alkyl 2-[1-(4-cyano-1,5-diphenyl-1H-pyrazol-3-yl)ethylidene]hydrazinecarbodithioate and pyrimidine-2-thione derivatives with appropriate hydrazonoyl halides. The structures of all the newly synthesized compounds were confirmed by elemental analyses, spectral data, and alternative route of synthesis whenever possible.